Statistics with SPSS for research - Tay, Choo Chuan (Penerbit Universiti Teknikal Malaysia Melaka, 2011)
Many students are having difficulties in learing Statistics. For the purpose of helping students to master the skills of this subjects, step by step easy approach has been designed and adopted by the authors of this book, This is deemed as the best approach when the design of the content is structured and well-organized.